Evaluation of Remote Sensing Data for the Identification of Lake-Stream Behavior during Normal and Cyclonic Seasons: The Case of Lake Alaotra, Madagascar - Rabotovao Sebas David; Ratsimbazafy Aro Pascal; Andriazafinahazo Fridolin; Rajaonah Rabevala; Razafindrazanakolona Andrianjafimanjato Daniel; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
Employing a synergistic approach integrating remote sensing and environmental science, this investigation rigorously examined the spatio-temporal dynamics of Lake Alaotra, Madagascar, under baseline seasonal conditions. The study elucidates the significant potential of satellite-derived data, coupled with advanced geospatial analytics, for precise mapping and comprehensive monitoring of intricate hydrological systems within diverse environmental contexts. Multi-temporal satellite imagery facilitated the accurate delineation of the lake's spatial extent, the quantification of seasonal fluctuations in its surface area, and the detection of inter-annual changes. Multivariate analysis of environmental covariates, including climatic oscillations, anthropogenic pressures, and inherent topographical attributes, enabled the identification and hierarchical prioritization of factors influencing the lake's hydrological regime. These findings yield critical evidence-based insights for informed decision-making in water resource management and environmental conservation strategies within Madagascar. Furthermore, scenario-driven predictive modeling of future hydrographic network modifications provides a crucial anticipatory framework for addressing potential challenges related to water availability across the nation, thereby enabling proactive planning and the implementation of targeted adaptation measures to mitigate adverse impacts. This research underscores the indispensable and evolving role of remote sensing technologies in the continuous monitoring of vital water resources and environmental integrity, demonstrating the efficacy of combining satellite data streams, sophisticated analytical methodologies, and remote sensing expertise to address salient environmental challenges in ecologically sensitive regions such as Madagascar.